2020
DOI: 10.7196/sajch.2020.v14i3.1567
|View full text |Cite
|
Sign up to set email alerts
|

Carers’ knowledge of treatment of severe acute malnutrition at Dadaab refugee complex, Kenya: A prospective cohort study

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0. Globally, about 55 million children under the age of 5 years (10%) are undernourished. Of these, 19 million suffer from severe acute malnutrition (SAM). [1] SAM contributes to about one million deaths every year in children under the age of 5 years. [1,2] Most SAM cases are from sub-Saharan Africa and South Asia. [3] The prevalence of SAM is generally higher in emergency contexts and contributes to about half of the deaths in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
2
2
1
Order By: Relevance
“… 21 Studies in India, 22 Bangladesh 15 , and Democratic Republic of Congo 14 also reported comparable levels of achievement of weight gain among children with complicated SAM. In contrast, higher proportion of treated patients achieved adequate weight gain in this study when compared with other studies conducted in the Dadaab refugee camp of Kenya 23 and Jimma university referral hospital of Ethiopia. 24 The proportion of treated children who achieved adequate weight gain was also higher than the level reported from India.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“… 21 Studies in India, 22 Bangladesh 15 , and Democratic Republic of Congo 14 also reported comparable levels of achievement of weight gain among children with complicated SAM. In contrast, higher proportion of treated patients achieved adequate weight gain in this study when compared with other studies conducted in the Dadaab refugee camp of Kenya 23 and Jimma university referral hospital of Ethiopia. 24 The proportion of treated children who achieved adequate weight gain was also higher than the level reported from India.…”
Section: Discussioncontrasting
confidence: 95%
“…This was consistent with other findings where weight gain varied between TFUs, as explained by a study conducted in Dadaab refugee camp in Kenya. 23 In addition, other studies conducted on non-refugee populations in Ethiopia also reported existence of differences between compared TFUs in Debre Birhan, 36 East Amhara, 17 and Mekele. 19 This could be due to differences in the level of care provided in the facilities, staffing, and the condition of patients admitted to the centers.…”
Section: Discussionmentioning
confidence: 92%
“…The first theme demonstrated that caregivers' characteristics could influence outpatient malnutrition management. Our results are consistent with other CMAM program evaluations showing that caregivers in low‐resource settings may have a limited understanding of malnutrition (Isanaka et al, 2020; Mbogo et al, 2020; Peter et al, 2019; Ware, 2018). Our findings showed that most caregivers associated malnutrition with weight loss, having difficulty identifying other signs.…”
Section: Discussionsupporting
confidence: 91%
“…The first theme demonstrated that caregivers’ characteristics and practices could influence malnutrition management. Our results are consistent with evaluations of other CMAM programs showing that caregivers in low-resource settings may have limited understandings of malnutrition (Isanaka et al, 2020; Mbogo et al, 2020; Peter et al, 2019; Ware, 2018). Our findings showed that most caregivers associated nutrition with weight loss, having more difficulty identifying other signs of malnutrition.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with other evaluations of CMAM programs in LMICs showing that caregivers in low-resource settings may have limited understanding of malnutrition and its complex mechanisms. [51][52][53][54] Our findings showed that most caregivers perceived undernutrition as being associated with weight loss and caused by poor feeding habits. Interestingly, a study conducted in India concluded that caregivers did not perceive malnutrition as a disease and were less likely to consult health professionals if their children were 'only skinny'.…”
Section: Discussionmentioning
confidence: 62%